Tathwir al- Manahij Bi syaklin 'Am fi al-Marhalah al-Asasiyah (al-Ibtidaiyah) fi al-Mamlakah al-Arabiyah as-Sa'udiyah - Akhmad Nurul Kawakip; Ali Hammad Al Balawi; Firman Nurul Fauzi (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2022)
Purpose- The purpose of this study is to see the reality of curriculum, curriculum development and evaluation from the point of view of teachers in elementary schools in Saudi Arabia. The focus of this research is a sample of teachers who work in Tabuk schools in the academic year of 1442 H. Design/ Methodology/ Approach- The method used in this research is a survey. The research informants were 100 elementary school teachers in the city of Tabuk Saudi Arabia who were taken randomly. Because it is a survey research, the data is obtained through a questionnaire. Findings- The results of the study show that it takes the initiative of all stages of education in developing the curriculum in many aspects. In addition, it requires special formulation at all levels, integration, continuity between subjects, connecting knowledge and scientific life, focusing on scientific research skills, developing thinking and problem solving skills, and considering students. The needs and tendencies of learners, and the existing and expected aspirations of the Saudi society, as all aspects of this Kingdom curriculum need to be developed, updated and acted upon. Research Limitation/ Implications- This research could not be more in-depth due to the limited time of researchers in searching for data, even though this research can be used as a basis in helping to develop the curriculum at Tabuk Elementary School in Saudi Arabia. Kata kunci/ Keywords- Curriculum, Elementary School, Saudi Arabia